Analysis on the Variation Characteristics of Monthly Rainfall in Guangdong Province - XU Linchun; HUANG Dong; LIN Meilan (Renmin Zhujiang)
Taking the daily precipitation data of many rainfall stations in Guangdong Province from1981 to 2010 as the research samples,this paper recognizes the temporal and spatial variation ofmonthly rainfall in Guangdong Province further based on the PCI and regression analysis methodwith ARCGIS software. The results indicate that: The monthly rainfall in coastal areas isgreater than inland areas during flood season, but the distribution of the maximum value of monthlyaverage rainfall over the years is not obvious.The data for inland areas is more stable than thatfor coastal area, and the peak value is not obvious in the year;There are obvious differencesin the spatial distribution of rainfall in different month; The rainfall intensity increases inflood season and decreases in non-flood season; The concentration degree of rainfall in the yearincreases, and the rainfall in the coastal areas of Guangdong Province is more concentrated thanthat in the inland areas.